Analisis Perhitungan Harga Pokok Produksi Dengan Pendekatan Activity Based Costing Pada Merta Jiwa Mebel - I Nengah Suardana; Putra, Cokorda Gde Bayu; Putu Nuniek Hutnaleontina (UNHI Press, 2025)
This research was conducted at Merta Jiwa Mebel with the main aim of identifying unit production costs using the activity-based costing (ABC) method and comparing the results with the conventional system currently implemented by the company. Precise determination of the cost of goods manufactured is essential for supporting effective business decisions. Using a qualitative descriptive approach, data were collected through interviews, direct observation, and documentation. The results show that the unit production cost calculated with the ABC method is Rp457,997 for door frames, Rp465,493 for window frames, Rp1,173,048 for door leaves, and Rp391,824 for window leaves. The findings imply that Merta Jiwa Mebel should adopt the ABC system in its cost calculations, as this approach enables a more precise distribution of production expenses by allocating overhead costs according to suitable cost drivers.